Reinforcing structure for structure

The reinforcement structure addresses the fire safety concerns and adhesion issues in existing methods by using an aqueous epoxy primer and polymer cement mortar with an admixed layer, enhancing the structural reinforcement and ensuring fire safety.

JP2025070865APending Publication Date: 2025-05-02NIPPON STEEL CHEM & MATERIAL CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023181453
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing reinforcement methods for structures often rely on combustible materials for bonding, which poses fire safety risks and may not ensure adequate adhesion performance between the primer and binder layers.

Method used

A reinforcement structure that uses an aqueous epoxy primer as the primer layer and a polymer cement mortar as the binder layer, with an admixed layer formed by mixing the primer and mortar at their boundary, eliminating the need for combustible materials and enhancing adhesion.

Benefits of technology

The proposed solution effectively improves the adhesion performance between the primer and binder layers without using dangerous materials, thereby enhancing the structural reinforcement while ensuring fire safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025070865000001_ABST
    Figure 2025070865000001_ABST
Patent Text Reader

Abstract

To form a primer layer and a binder layer without using a dangerous substance in the Fire Service Act, and to improve adhesion performance between the primer layer and the binder layer.SOLUTION: A reinforcing structure of a structure in which a reinforcing material made of a fiber-reinforced plastic containing reinforcing fibers is bonded to the surface of the structure using a binder, wherein a primer layer formed of an aqueous epoxy primer having an aqueous epoxy resin main agent and a curing agent, and a binder layer arranged on the surface of the primer layer, formed of polymer cement mortar as the binder, and having an admixture layer in which the aqueous epoxy primer and the polymer cement mortar are admixed at a boundary with the primer layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a reinforcing structure for a structure. [Background technology]

[0002] In recent years, as a reinforcing structure for existing or newly constructed structures, there have been known continuous fiber sheet bonding methods, such as a carbon fiber sheet bonding method and an aramid fiber sheet bonding method, in which a continuous fiber-reinforced sheet, such as a carbon fiber sheet or an aramid fiber sheet, is attached to or wrapped around the surface of a structure, as described in Patent Document 1, or a method in which a sheet in which a continuous fiber bundle is impregnated with uncured matrix resin is bonded and then cured.

[0003] Additionally, in order to eliminate the need for on-site resin impregnation, an FRP plate adhesive reinforcement method has been developed in which factory-produced FRP plates with a thickness of 1 to 2 mm and a width of approximately 5 cm are adhered to the concrete surface using a putty-like adhesive resin.

[0004] Furthermore, Patent Document 2 discloses a reinforcement structure for a structure, in which fiber reinforcement is impregnated with a matrix resin, multiple hardened continuous fiber-reinforced plastic wires are aligned in a curtain-like shape in the longitudinal direction, and the wires are fixed to each other with a wire fixing material (hereinafter, sometimes simply referred to as a "fiber-reinforced sheet"), and this is bonded to the surface of the structure with a bonding material to form an integrated structure.

[0005] In these methods, combustible materials (specifically, for example, hazardous materials under the Fire Service Act) are generally used as a binder for bonding a reinforcing material such as a fiber-reinforced sheet to a structure.

[0006] On the other hand, Patent Document 3 describes the use of a flame-retardant cement-based material as a binder. In Patent Document 3, an epoxy resin primer is applied to the surface of a structure, a joint adhesive is applied on top of that, and a cement-based binder is poured on top of that. In the examples in Patent Document 3, a room temperature curing epoxy resin ("FJ-C Primer" (product name) manufactured by Nippon Steel Composites Corporation / currently FP-WEC manufactured by Nippon Steel Chemical & Material Co., Ltd.) is used as the joint adhesive, which is combustible. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 3-224901 [Patent Document 2] JP 2008-63758 A [Patent Document 3] JP 2011-208352 A Summary of the Invention [Problem to be solved by the invention]

[0008] Patent Document 3 also discloses that an epoxy emulsion adhesive (water-based primer) can be used as a joint adhesive, but there is a concern that if a non-combustible water-based primer is used as a joint adhesive, the adhesion performance between the primer layer formed with the primer and the binder layer formed with the binder of the cement-based material may not be sufficiently ensured. For this reason, the reality is that a resin-based adhesive, which is combustible but has high adhesion performance, is used as a primer (joint adhesive).

[0009] The object of the present invention is to provide a reinforcement structure for a structure in which a reinforcing material made of fiber-reinforced plastic containing reinforcing fibers is adhered to the surface of the structure using a binder, the reinforcement structure for the structure comprising a primer layer formed from a primer and a binder layer disposed on the surface of the primer layer and formed from the binder, in which the primer layer and the binder layer can be formed without using hazardous materials as defined by the Fire Service Act, and the adhesion performance between the primer layer and the binder layer can be improved. [Means for solving the problem]

[0010] The first embodiment of the reinforcing structure is a reinforcing structure for a structure in which a reinforcing material made of fiber-reinforced plastic containing reinforcing fibers is adhered to the surface of the structure using a binder, and the reinforcing structure comprises a primer layer formed from an aqueous epoxy primer having an aqueous epoxy resin base and a curing agent, and a binder layer disposed on the surface of the primer layer, formed from polymer cement mortar as the binder, and having a mixed layer at the boundary with the primer layer in which the aqueous epoxy primer and the polymer cement mortar are mixed.

[0011] In the reinforced structure of the first embodiment, the primer layer is formed from a non-combustible water-based epoxy primer, and the binder layer is formed from a non-combustible polymer cement mortar.

[0012] Furthermore, in the reinforced structure of the first embodiment, the binder layer has a mixture layer of the water-based epoxy primer and the polymer cement mortar at the boundary with the primer layer, which makes the primer layer and the binder layer less likely to peel off, improving the adhesion performance between the primer layer and the binder layer.

[0013] Therefore, according to the reinforced structure of the first aspect, the primer layer and the binder layer can be formed without using any hazardous materials under the Fire Service Act, and the adhesion performance between the primer layer and the binder layer can be improved.

[0014] The reinforcing structure of the second embodiment is the same as that of the first embodiment, in which the reinforcing material is any one of a fiber-reinforced sheet in which a plurality of fiber-reinforced plastic wires are aligned in a curtain-like shape in the longitudinal direction and fixed to each other with a wire fixing material, a fiber-reinforced plastic lattice material, a fiber-reinforced plastic plate, and a fiber-reinforced plastic rod-shaped body.

[0015] In the reinforcement structure of the third aspect, in the first or second aspect, the reinforcing material is embedded inside the binder layer, and the surface of the reinforcing material has projections and recesses.

[0016] In the third embodiment of the reinforcement structure, the reinforcing material has an uneven surface, which provides an anti-slip effect and enhances adhesion between the reinforcing material and the polymer cement mortar, thereby firmly bonding the reinforcing material and the binder and preventing the reinforcing material from peeling off from the binder before it breaks.

[0017] In the reinforced structure of the fourth aspect, in the third aspect, the reinforcing material has a surface on which a powder having an average particle size of 0.900 mm or less is applied at a rate of 0.2 to 2.0 kg / m 2 It is attached.

[0018] Here, the adhesion weight of the reinforcing material is 0.2 kg / m 2 When the adhesion weight of the reinforcing material is less than 2.0 kg / m 2 If the thickness exceeds this value, the surface irregularities of the reinforcing material will be small, so the anti-slip effect of the powder will be small and the adhesion between the reinforcing material and the polymer cement mortar will be low, and the reinforcing material may peel off from the binder before it breaks or before the polymer cement mortar experiences cohesive failure.

[0019] Furthermore, if the average particle size of the powder exceeds 0.900 mm, when the reinforcing material is pressed into the concrete to be embedded, the powder tends to get caught on a pressing tool such as a rubber spatula, decreasing workability.

[0020] In contrast, in the reinforced structure of the fourth embodiment, as described above, the powder attached to the surface of the reinforcing material has an average particle size of 0.900 mm or less and a pressure of 0.2 to 2.0 kg / m 2 Since the powder is attached, the anti-slip effect of the powder maintains high adhesion between the reinforcing material and the polymer cement mortar while also preventing any deterioration in workability.

[0021] As a result, poor application can be suppressed while preventing the reinforcing material from breaking or peeling off from the binder before the polymer cement mortar experiences cohesive failure. Effect of the Invention

[0022] According to the reinforcement structure of the present invention, a reinforcement structure for a structure is provided in which a reinforcing material made of fiber-reinforced plastic containing reinforcing fibers is adhered to the surface of the structure using a binder, and the reinforcement structure for the structure includes a primer layer formed from a primer and a binder layer disposed on the surface of the primer layer and formed from the binder, and the primer layer and the binder layer can be formed without using hazardous materials as defined by the Fire Service Act, and the adhesion performance between the primer layer and the binder layer can be improved. [Brief description of the drawings]

[0023] [Figure 1] 1 is a schematic cross-sectional view showing a reinforcement structure according to an embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view for explaining a base treatment process in a construction method for a reinforcement structure according to the present embodiment. FIG. [Diagram 3] 4 is a schematic cross-sectional view for explaining a primer application step in the construction method of the reinforcement structure according to the present embodiment. FIG. [Figure 4] 1 is a schematic cross-sectional view for explaining a mortar application step in the construction method of the reinforcement structure according to the present embodiment. FIG. [Diagram 5] FIG. 2A shows a fiber-reinforced sheet according to the present embodiment, and FIG. 2B shows a fiber-reinforced plastic strand of the fiber-reinforced sheet according to the present embodiment. [Figure 6] FIG. 11 is a perspective view showing another example of a reinforcing material. [Figure 7] FIG. 11 is a perspective view showing another example of a reinforcing material. [Figure 8] FIG. 1 is an explanatory diagram of a three-point bending test. [Figure 9] FIG. [Figure 10] FIG. 1 is a schematic diagram of a test piece for a single-sided tensile shear test. [Figure 11] FIG. 2 is an explanatory diagram of a one-way tensile shear test. [Figure 12] Table 1 shows the evaluation results. [Figure 13] 1 is a table showing the average particle size of various inorganic powders. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, an example of an embodiment of the present invention will be described with reference to the drawings.

[0025] In this specification, a numerical range indicated using "to" means a range including the numerical values ​​before and after "to" as the minimum and maximum values, respectively. In addition, in a numerical range described in a stepped manner in this specification, an upper limit or lower limit value described in a certain numerical range may be replaced with an upper limit or lower limit value of another stepped numerical range. In addition, in a numerical range described in this specification, an upper limit or lower limit value described in a certain numerical range may be replaced with a value shown in an example. In this specification, the amount of each component means the total amount of multiple substances when there are multiple substances corresponding to each component, unless otherwise specified.

[0026] <Reinforcement structure 10> 1, the reinforcement structure 10 according to this embodiment is a reinforcement structure for a structure 90 in which a fiber-reinforced sheet 40 as a reinforcing material is bonded to a surface 90A of the structure 90 using a binder. It has been found that the reinforcement structure 10 can reinforce the structure 90 while reducing the use of hazardous materials (flammable materials) under the Fire Service Act (including reducing the amount of use to zero) by using an aqueous epoxy primer 20, a polymer cement mortar 50 as a binder, and the fiber-reinforced sheet 40. The reinforcement structure 10 has a primer layer 22 formed by the aqueous epoxy primer 20, a binder layer 52 formed by the polymer cement mortar 50, and the fiber-reinforced sheet 40.

[0027] In the following, first, the structure 90, the primer layer 22, the water-based epoxy primer 20, the binder layer 52, the polymer cement mortar 50, and the fiber-reinforced sheet 40 will be described. Then, the construction method of the reinforced structure 10, the action and effect of the reinforced structure, and the evaluation test of the reinforced structure will be described.

[0028] <Structure 90> An example of the structure 90 to be reinforced by the reinforcement structure 10 according to this embodiment is a concrete structure. An example of the concrete structure is a bridge deck. Examples of the concrete structure include a reinforced concrete structure having reinforcing bars inside, and an unreinforced concrete structure having no reinforcing bars inside.

[0029] In addition, concrete structures are not limited to bridge decks, but may include, for example, structures other than bridge decks (e.g., bridge girders and piers), tunnels, buildings, etc., as long as they are structures made of concrete.

[0030] Furthermore, the structure 90 is not limited to a concrete structure, but may be, for example, a structure made of mortar, ceramics, metal, glass, or the like, as long as it is a structure to be reinforced.

[0031] Hereinafter, the surface 90A of the structure 90 reinforced by the reinforcing structure 10 according to the present embodiment may be referred to as the reinforced surface 90A. The reinforced surface 90A is, for example, the bottom surface of the structure 90 facing downward (specifically, downward in the direction of gravity). The reinforced surface 90A may be a side surface of the structure 90 (specifically, a surface along the direction of gravity or a surface inclined with respect to the direction of gravity), and in the present embodiment, the reinforced surface 90A is, for example, a surface on which the polymer cement mortar 50 may drip (i.e., a surface excluding a horizontal surface facing upward in the direction of gravity).

[0032] <Primer layer 22> The primer layer 22 is disposed on the surface 90A to be reinforced of the structure 90, and is a layer formed from the water-based epoxy primer 20. This primer layer 22 is a base layer formed as a base for the binder layer 52. In this embodiment, the primer layer 22 is formed by applying the water-based epoxy primer 20 to the surface 90A to be reinforced of the structure 90 (see <Primer application step> described later).

[0033] It should be noted that another primer layer (base layer) may be formed between the primer layer 22 and the structure 90. That is, the primer layer may be formed of a plurality of layers. When another primer layer is formed between the primer layer 22 and the structure 90, the other primer layer may be formed of a hazardous material defined in the Fire Service Act, or may be formed of a non-hazardous material that does not fall under the category of hazardous material (for example, a non-combustible material such as a water-based primer). That is, the material of the other primer layer is not limited.

[0034] <Water-based epoxy primer 20> The water-based epoxy primer 20 is an epoxy resin primer using water as a medium, and has the advantage of having a higher shear strength than water-based acrylic primers, so the water-based epoxy primer is used in the present invention. There are water-based epoxy primers that use water-soluble epoxy resins and emulsion types, each of which is further divided into one-component curing type and two-component curing type, but the one preferably used in the present invention is the two-component water-based epoxy primer 20 of emulsion type having an epoxy resin main agent of emulsion type and a curing agent. The water-based epoxy primer 20 can be used in a ratio predetermined according to the materials used (for example, the main agent and the curing agent are mixed in a weight ratio of 100:100). In addition, from the viewpoint of repairing concrete structures, a viscosity of 100 mPa·s or less is preferable because it increases the permeability.

[0035] The epoxy of the water-based epoxy primer is exemplified by bisphenol type epoxy such as bisphenol A type epoxy, and epoxy modified with acrylic resin, etc., but acrylic modified epoxy is preferable. The curing agent is not particularly limited as long as it is a water-soluble amine-based curing agent. Specifically, as the water-based epoxy primer 20, for example, FP primer FP-EE manufactured by Nippon Steel Chemical & Material Co., Ltd. can be used.

[0036] <Binder layer 52> The binder layer 52 is disposed on the surface of the primer layer 22, and is a layer formed of polymer cement mortar 50. This binder layer 52 has a mixed layer 29 in which the water-based epoxy primer 20 and the polymer cement mortar 50 are mixed at the boundary with the primer layer 22. The binder layer 52 is formed by applying the polymer cement mortar 50 to the reinforced surface 90A of the structure 90 to which the water-based epoxy primer 20 has been applied (see <Mortar application process> described later).

[0037] The miscible layer 29 is formed, for example, by satisfying at least the following conditions (1) to (3). (1) The water-based epoxy primer 20 is a two-component type consisting of a base agent and a curing agent, and the curing agent is water-soluble. (2) Applying the polymer cement mortar 50 when the coating film of the water-based epoxy primer 20 is in the early stage of polymerization and contains more than 10 wt % moisture. (3) The water-based epoxy primer 20 before hardening and the polymer cement mortar 50 before hardening have an affinity to be mixed with each other.

[0038] Specifically, the miscible layer 29 is formed on the binder layer 52 side of the interface between the primer layer 22 and the binder layer 52. Here, the miscible layer 29 is a layer in which the epoxy resin component of the water-based epoxy primer 20 is mixed and integrated with the polymer cement mortar 50, and it is presumed that the epoxy resin component of the primer 20 bonds with the calcium hydroxide in the polymer cement mortar 50, thereby strengthening the adhesion between the primer layer and the polymer cement layer.

[0039] When the cross section of the applied area is observed using, for example, an SEM-EPMA (electron probe microanalyzer) or SEM-EDX (energy dispersive X-ray spectroscopy, also known as SEM-EDS), the mixed layer 29 can be observed as a layer approximately 10 to 50 μm thick in which the distribution of carbon derived from the water-based epoxy primer and the distribution of calcium derived from the polymer cement mortar 50 overlap.

[0040] As described above, the mixed layer 29 is formed so that the primer layer 22 is mixed with the binder layer 52, and therefore the distribution of carbon derived from the primer is observed to decrease continuously from the primer layer 22 toward the binder layer 52, but since the base (the reinforced surface 90A of the structure 90) is a rough surface having irregularities, the primer layer 22 is also likely to have localized unevenness. For this reason, the primer layer 22, the binder layer 52, and the mixed layer 29 are not necessarily observed in a uniform state over the entire surface of the primer layer 22 and the binder layer 52, and the primer layer 22 and the mixed layer 29 cannot be clearly distinguished, and it may be observed as if only the mixed layer 29 exists.

[0041] <Polymer Cement Mortar 50> The polymer cement mortar 50 is a cement composite material that includes cement, fine aggregate, a cement-mixable polymer, and reinforcing organic fibers.

[0042] The cement can be selected in consideration of the on-site construction conditions, and is not particularly limited. For example, various Portland cements such as ordinary, early strength, moderate heat, and extra early strength, various mixed cements such as blast furnace cement in which fly ash or blast furnace slag is mixed with any of these Portland cements, rapid hardening cements, etc. can be used alone or in combination of two or more types.

[0043] In addition, known admixtures such as blast furnace slag powder, fly ash, silica fume, limestone powder, quartz powder, gypsum dihydrate, gypsum hemihydrate, anhydrous gypsum, quicklime-based expanding materials, and calcium sulfoaluminate-based expanding materials can be added to the cement.

[0044] As the fine aggregate, river sand, sea sand, mountain sand, crushed sand, No. 3 to No. 8 silica sand, limestone, slag fine aggregate, etc. can be used, and it is preferable to use fine aggregate such as silica sand and limestone whose grain size is adjusted and which does not contain fine powder or coarse aggregate. The mixing ratio can be 25 to 300 parts by mass, preferably 50 to 230 parts by mass, per 100 parts by mass of the above cement.

[0045] Examples of polymers for mixing with cement include liquid polymer emulsions and re-emulsified powder resins, and those specified in JIS A 6203 can be used. Specific examples include resins such as polyacrylic ester, styrene butadiene, ethylene vinyl acetate, vinyl acetate / vinyl versatate, and vinyl acetate / vinyl versatate / acrylic ester, and any of these can be appropriately selected and used alone or in combination as an emulsion.

[0046] Examples of reinforcing organic fibers include ultra-high molecular weight polyethylene fibers, vinylon fibers, nylon fibers, polyparaphenylene benzobisoxazole fibers (PBO fibers), para-aramid fibers, polyarylate fibers, etc., and one or more of these can be used in combination. The reinforcing organic fibers have, for example, a fiber length of 3 to 20 mm and an aspect ratio of 100 to 4000, and are mixed in an amount of 0.5 to 2.0 vol% into the polymer cement mortar 50.

[0047] In addition to the above materials, polymer cement mortar 50 may contain additives such as a setting retarder, a hardening accelerator, a thickener, an antifoaming agent, a foaming agent, an anti-rust agent, an antifreeze agent, a colorant, a water retention agent, a shrinkage reducing agent, and an expansion agent.

[0048] <Fiber reinforced sheet 40> 5(A), the fiber-reinforced sheet 40 is a sheet material that is adhered to a surface 90A to be reinforced of a structure 90 with polymer cement mortar 50 as a binder, thereby reinforcing the structure 90. This fiber-reinforced sheet 40 is formed by arranging a plurality of fiber-reinforced plastic wires 43 containing reinforcing fibers 42 in a curtain-like shape in the longitudinal direction and fixing the wires to each other with a wire fixing material. In this embodiment, the fiber-reinforced sheet 40 is disposed within the binder layer 52 of the polymer cement mortar 50 by being embedded therein.

[0049] As the reinforcing fiber 42, for example, organic fibers such as aramid, PBO (polyparaphenylene benzbisoxazole), polyamide, polyarylate, polyester, etc., basalt fiber, fly ash fiber, carbon fiber, glass fiber, metal fiber such as steel fiber, etc., can be used alone or in combination of two or more kinds. However, examples of reinforcing fibers are not limited to these.

[0050] Specifically, as shown in Fig. 5(A)(B), a fiber sheet (so-called strand sheet) can be used as the fiber-reinforced sheet 40, in which a plurality of fiber-reinforced plastic strands 43 including reinforcing fibers 42 are aligned in a curtain-like shape in the longitudinal direction and the strands 43 are fixed to each other with a strand fixing material 45. As shown in Fig. 5(B), the fiber-reinforced plastic strands 43 are formed by impregnating the reinforcing fibers 42 with a matrix resin 47 and curing the matrix resin 47. For the matrix resin 47, a thermosetting resin such as a room-temperature curing or thermosetting epoxy resin, vinyl ester resin, acrylic resin, unsaturated polyester resin, or phenol resin, or a thermoplastic resin such as an in-situ polymerization type phenoxy resin, nylon, or vinylon can be used. Preferably, an epoxy resin, which is a thermosetting resin, is used.

[0051] In the fiber reinforced sheet 40, the spacing between the fiber reinforced plastic strands 43 is, for example, 0.05 mm or more and 10 mm or less. In this embodiment, since polymer cement mortar is used as the binder, the spacing between the fiber reinforced plastic strands 43 is, for example, more than 3 mm. If it is 3 mm or less, the spacing between the fiber reinforced plastic strands 43 is narrow, and it is difficult for the polymer cement mortar 50 to pass between the fiber reinforced plastic strands 43 of the fiber reinforced sheet 40. On the other hand, if the spacing between the fiber reinforced plastic strands 43 exceeds 10 mm, the number of fiber reinforced plastic strands 43 per unit area of ​​the fiber reinforced sheet 40 decreases, and the reinforcing effect decreases.

[0052] <Inorganic Powder Used in Fiber Reinforced Sheet 40> In the fiber reinforced sheet 40 used in this embodiment, for example, inorganic powder is attached to the outer periphery of a plurality of fiber reinforced plastic strands 43. By attaching inorganic powder to the outer periphery of a plurality of fiber reinforced plastic strands 43, unevenness is formed on the surface of the fiber reinforced sheet 40, and the unevenness is embedded in the binder, thereby exerting an anchor effect.

[0053] The inorganic powder attached to the fiber-reinforced sheet 40 has an average particle size (D50) of, for example, 0.900 mm or less in the particle size distribution measured according to JIS Z 2601, and a weight per unit area of ​​the fiber-reinforced sheet 40 of 0.2 to 2.0 kg / m 2 It is attached.

[0054] Specifically, the inorganic powder may be selected from crushed silica sand No. 4 (average particle size: 0.887 mm), No. 5 (average particle size: 0.511 mm), No. 6 (average particle size: 0.294 mm), No. 7 (average particle size: 0.129 mm), and No. 8 (average particle size: 0.073 mm), or a mixture thereof; crushed stone such as Hakuryu crushed stone of 1 rin (average particle size: 0.4 mm), 2 rin (average particle size: 0.7 mm), and 3 rin (average particle size: 1.0 mm), etc. These can be crushed ashstone, fine aggregate of blast furnace slag of similar particle size as above, fine aggregate of natural materials such as river sand, sea sand, mountain sand and crushed sand, fine powder of ceramic materials such as graphite, silica and alumina, or mixtures thereof, but taking into consideration cost and workability, silica sand selected from No. 4, No. 5, No. 6 and No. 7 silica sand, or 1 rin, 2 rin or 3 rin Hakuryu crushed stone and mixtures of these silica sands and Hakuryu crushed stone are more preferable (see Figure 13).

[0055] The diameter of the inorganic powder is, for example, smaller than the diameter of the fiber reinforced plastic strands 43, and the ratio of the diameter of the fiber reinforced plastic strands 43 of the fiber reinforced sheet 40, the spacing between the fiber reinforced plastic strands 43, and the diameter of the inorganic powder is, for example, 1:0.5-5:0.03-1.

[0056] In this embodiment, inorganic powder is used as an example of the powder, but the powder is not limited thereto. For example, the powder may be an organic powder made of an organic material such as a synthetic resin, in addition to an inorganic material. The powder is attached by using an adhesive or binder, or by softening the matrix resin of the fiber-reinforced plastic strand 43 by heating or the like, and fusing or welding the matrix resin.

[0057] <Modifications of the fiber-reinforced sheet 40> In the above embodiment, the fiber reinforced sheet 40 shown in Figs. 5(A) and (B) is used as an example of a reinforcing material, but the present invention is not limited to this.

[0058] The fiber-reinforced sheet 40 is a fiber-reinforced sheet in which a plurality of fiber-reinforced plastic strands 43 including reinforcing fibers 42 are aligned in the longitudinal direction and fixed to each other with a strand fixing material, and the strands 43 may be bundled into a belt shape, arranged with an interval of 3 to 5 mm between each belt, and fixed with a wire fixing material. Note that the width of the belt portion in which the strands 43 are bundled is preferably about 5 to 50 mm, and other shapes and the like are similar to those of the fiber-reinforced plastic strands 43. The structure of the belt portion is not particularly limited, and it may be fastened using a wire fixing material, or may be fused using an adhesive.

[0059] An example of the reinforcing material may be, for example, a fiber-reinforced sheet 140 shown in FIG. 6, and may be any reinforcing material containing reinforcing fibers. The fiber-reinforced sheet 140 shown in FIG. 6 includes a fiber layer 144 in which reinforcing fibers 42 are arranged in one direction (X direction in FIG. 6), and a support layer 146 that supports the fiber layer 144. The support layer 146 is disposed on one side of the fiber layer 144 and is configured as a mesh-shaped support sheet that supports the fiber layer 144. The support layer 146 suppresses the reinforcing fibers 42 of the fiber layer 144 from coming apart. The support layer 146 may be disposed on both sides of the fiber layer 144, and may not include the support layer 146 as long as the reinforcing fibers 42 are suppressed from coming apart in some way.

[0060] Also, as the reinforcing material, for example, a plate made of fiber-reinforced plastic may be used. As the plate, for example, a fiber-reinforced plate (so-called FRP plate) in which a fiber-reinforced sheet in which reinforcing fibers 42 are arranged in one direction is impregnated with resin and the resin is hardened can be used. In this case, as the resin to be impregnated into the fiber-reinforced sheet, a thermosetting resin such as a room temperature curing type or a thermosetting type epoxy resin, a vinyl ester resin, an acrylic resin, an unsaturated polyester resin, or a phenolic resin, or a thermoplastic resin such as an in-situ polymerization type phenoxy resin, nylon, or vinylon can be used, and preferably, an epoxy resin, which is a thermosetting resin, is used. Also, the amount of resin impregnated into the fiber-reinforced sheet 40 is 30 to 70% by weight, preferably 40 to 60% by weight.

[0061] The reinforcing material may be a fiber-reinforced sheet in which a plurality of band-shaped FRP plates (one example of fiber-reinforced plastic wires) containing reinforcing fibers 42 are arranged at equal intervals so as to be parallel to the longitudinal direction and the FRP plates are fixed to each other with a wire fixing material. The width of the band-shaped FRP plate is preferably 10 to 50 mm, and the plate thickness and the intervals between the FRP plates are similar to those of the fiber-reinforced sheet using fiber-reinforced plastic wires 43.

[0062] As the reinforcing material, a lattice material made of fiber-reinforced plastic may be used as shown in Fig. 7. Examples of the lattice material include those formed by arranging a plurality of fiber-reinforced plastic wires 43 containing reinforcing fibers 42 in a lattice pattern, and those formed by laminating and curing a plurality of bundles of reinforcing fibers aligned in one direction and impregnating them with a matrix resin such as epoxy resin. The opening shape of the lattice may be a triangle, a square, a hexagon, or a combination of these.

[0063] Also, a fiber-reinforced plastic rod may be used as the reinforcing material. The rod may be one in which reinforcing fiber 42 is processed into a rod shape by pultrusion molding, or one in which a plurality of fiber-reinforced plastic wires 43 containing reinforcing fiber 42 are twisted together. A plurality of rods may be arranged side by side for use.

[0064] Furthermore, the reinforcing material may have powder (including inorganic powder and organic powder) attached thereto, depending on the type of binder, or may have no powder attached thereto.

[0065] <Other examples of unevenness in reinforcing materials> In this embodiment, the irregularities are formed on the surface of the fiber-reinforced sheet 40 by adhering inorganic powder to the surface of the fiber-reinforced sheet 40 as a reinforcing material, but the present invention is not limited to this. The surface of a reinforcing material such as the fiber-reinforced sheet 40 may be roughened using shot blasting or a metal brush to form irregularities on the surface of the reinforcing material, or the diameter of a rod-shaped body may be intermittently changed to provide male screw-like irregularities.

[0066] <Other examples of adhesion of reinforcing materials> In this embodiment, the fiber-reinforced sheet 40 is embedded inside the binder layer 52 made of polymer cement mortar 50 and placed within the binder layer 52, thereby adhering to the polymer cement mortar 50 as a binder, but this is not limited to this.

[0067] The reinforcing material including the fiber-reinforced sheet 40 may be bonded by an adhesive layer arranged (laminated) on the surface of the binder layer 52. In this case, the reinforcing material is, for example, embedded inside the adhesive layer and arranged inside the adhesive layer, thereby being bonded to the adhesive layer. In this way, the reinforcing material only needs to be directly or indirectly bonded to the binder, and in this case, it is not necessarily necessary to attach particles to the surface of the reinforcing material. In addition, the adhesive layer may be formed of a hazardous material under the Fire Service Act, or may be formed of a non-hazardous material that does not fall under the hazardous material (for example, a non-flammable material such as a water-based primer). In other words, the material of the adhesive layer is not limited. <An example of a construction method for the reinforcement structure 10> An example of a construction method for the reinforcement structure 10 includes a base preparation step, a primer application step, a mortar application step, and an adhesion step. Each step of the construction method will be described below.

[0068] <Surface preparation process> In the surface preparation step (see FIG. 2), a surface preparation step is performed to remove protrusions, attachments, deteriorated layers, and the like from the reinforced surface 90A of the structure 90. Removal of the protrusions, attachments, and deteriorated layers is performed using removal means such as a disk sander, sand blasting, steel shot blasting, and water jet. Note that the surface preparation step is not essential, and does not have to be performed.

[0069] <Primer application process> In the primer application step (see FIG. 3), a water-based epoxy primer 20 is applied to the surface to be reinforced 90A of the structure 90. If a base preparation step has been performed, the water-based epoxy primer 20 is applied to the surface to be reinforced 90A that has been subjected to base preparation.

[0070] Through the primer application step, a primer layer 22 made of the water-based epoxy primer 20 is formed on the surface 90A of the structure 90 to be reinforced.

[0071] As described above, when another primer layer (base layer) is formed between the primer layer 22 and the structure 90, the primer that forms the other primer layer is applied to the reinforced surface 90A of the structure 90 prior to the primer 20. Then, the primer 20 is applied to the reinforced surface 90A of the structure 90 to which the primer has been applied.

[0072] <Mortar application process> The mortar application step is a step of applying polymer cement mortar 50 to the reinforced surface 90A of the structure 90 to which the water-based epoxy primer 20 has been applied. In the mortar application step, the polymer cement mortar 50 is applied before the water-based epoxy primer 20 hardens.

[0073] By the mortar application step, a binder layer 52 made of polymer cement mortar 50 is formed on the reinforced surface 90A (specifically, on the surface of the primer layer 22) of the structure 90 to which the water-based epoxy primer 20 has been applied. The thickness of the binder layer 52 is at least thicker than the fiber-reinforced sheet 40, for example, about 2 mm to 10 mm.

[0074] <Adhesion process> The adhesion step is a step in which, before the applied polymer cement mortar 50 hardens, the fiber reinforced sheet 40 is pressed against the applied layer of polymer cement mortar 50 to embed it and adhere it to the reinforced surface 90A of the structure 90. In this way, the fiber reinforced sheet 40 is disposed inside the mortar layer of polymer cement mortar 50.

[0075] The fiber reinforced sheet 40 is pressed with a roller or a rubber spatula, so that the air layer at the adhesive interface is expelled from the gaps between the fiber reinforced plastic strands 43, and the fiber reinforced sheet 40 is embedded and adhered to the mortar layer.

[0076] As described above, when the reinforcing material including the fiber-reinforced sheet 40 is adhered to an adhesive layer arranged (laminated) on the surface of the bonding material layer 52, for example, the adhesive that forms the adhesive layer is applied to the surface of the bonding material layer 52 prior to the bonding process, and then, before the applied adhesive hardens, the reinforcing material is pressed into the adhesive layer by being embedded therein and adhered to the reinforced surface 90A of the structure 90.

[0077] <Effects of this embodiment> The effects of this embodiment will be described.

[0078] In the reinforced structure 10 according to this embodiment, the primer layer 22 is formed from the water-based epoxy primer 20, which is a non-combustible material, and the binder layer 52 is formed from the polymer cement mortar 50, which is also a non-combustible material.

[0079] Furthermore, in the reinforced structure 10, the binder layer 52 has a mixture layer 29 in which the water-based epoxy primer 20 and the polymer cement mortar 50 are mixed at the boundary with the primer layer 22. Therefore, the primer layer 22 and the binder layer 52 are less likely to peel off, and the adhesion performance between the primer layer 22 and the binder layer 52 is improved.

[0080] Therefore, according to the reinforcement structure 10 of this embodiment, it is possible to form the primer layer 22 and the binder layer 52 without using hazardous materials under the Fire Service Act, and to improve the adhesion performance between the primer layer 22 and the binder layer 52.

[0081] In the reinforcement structure 10 according to this embodiment, inorganic powder having an average particle size of 0.900 mm or less is applied to the surface of the fiber reinforced sheet 40 at a rate of 0.2 to 2.0 kg / m 2 Therefore, the adhesiveness between fiber reinforced sheet 40 and polymer cement mortar 50 is maintained high due to the anti-slip effect of the inorganic powder.

[0082] In this case, if the adhesion at the interface between polymer cement mortar 50 and primer layer 22 is low, the application of an external force will cause destruction at the interface, making it impossible to obtain the desired reinforcing strength. However, in the reinforced structure 10 according to this embodiment, as described above, the binder layer 52 has a mixture layer 29 at the boundary with the primer layer 22, in which the water-based epoxy primer 20 and the polymer cement mortar 50 are mixed, so that the adhesion performance between the primer layer 22 and the binder layer 52 is improved, and the primer layer 22 and the binder layer 52 are less likely to peel off even when an external force is applied.

[0083] As a result, fiber reinforced sheet 40 can be prevented from peeling off from the interface between primer layer 22 and binder layer 52 before it breaks or polymer cement mortar 50 experiences cohesive failure.

[0084] <Evaluation test> In this test, the adhesion performance between the primer layer 22 and the binder layer 52 in the reinforcement structure 10 according to this embodiment was evaluated. Specifically, in this test, Examples 1 and 2 and Comparative Examples 1 to 4 were evaluated as follows.

[0085] [Three-point bending test] Test pieces were prepared in accordance with JIS R5201:2005 Physical Testing Methods for Cement, and a three-point bending test was performed using a universal testing machine (see Figure 8). In addition, a three-point bending test was performed using test pieces exposed under the following exposure conditions and test pieces before exposure. Exposure conditions: The test piece is immersed in hot water at 90°C for 3 days. As an initial screening for the evaluation of adhesion performance, a three-point bending test was carried out for Examples 1 and 2 and Comparative Examples 1 to 4. Specifically, the test results for the test pieces before exposure were 5.0 N / mm 2 The specimens that were above this were subjected to the adhesion strength test described below. On the other hand, the test results for the test pieces before exposure were 5.0N / mm 2 If the adhesion strength was less than 100%, it was determined that the adhesion performance was poor, and the adhesion strength test was not performed.

[0086] [Adhesion strength test] In this test, a bond strength test was conducted using the Construction Research Institute method (JSCE-K561: Test method for cross-section repair materials for concrete structures) (see Figure 9). In addition, similar to the three-point bending test, a three-point bending test was conducted using test pieces exposed under the following exposure conditions and test pieces before exposure. Exposure conditions: The test piece is immersed in hot water at 90°C for 3 days.

[0087] [One-way shear test] In this test, a one-way shear test was carried out using a JIS concrete slab (corresponding to structure 90), a fiber-reinforced sheet 40, a water-based epoxy primer 20, and a polymer cement mortar 50.

[0088] The reinforcing effect of the fiber-reinforced sheet 40 on a concrete body (corresponding to structure 90) has been confirmed when the fiber-reinforced sheet 40 itself is used for reinforcement using conventional epoxy resin. Here, the reinforcing effect was confirmed by evaluating the adhesion performance between the fiber-reinforced sheet and the concrete body when a non-hazardous material, which differs from the conventional construction method, was used by a one-way tensile shear test.

[0089] The test piece 100 for the single-sided shear test was prepared by applying water-based epoxy primer 20 to a JIS concrete flat plate 90 of 30 cm square after scraping, applying polymer cement mortar 50 in 3 rows with a thickness of 5 mm in a width of 4 cm, embedding fiber reinforced sheet 40 cut to a width of 4 cm and a length of 60 cm in 3 rows so that one side protrudes, and then curing in a 20°C environment for 2 weeks, and bonding a tab 99 made of epoxy resin and an aramid fiber sheet to one end of the fiber reinforced sheet 40 (see FIG. 10). The single-sided shear test was performed on the test piece 100 using a universal testing machine and a test piece fixing jig 102 as shown in FIG. 11, and evaluating the fracture load and fracture mode, and the evaluation of the integrity of the fiber reinforced sheet and the concrete member was performed with n=3. The criteria for judging pass / fail were based on the measured peel fracture energy Gf and observation of the fracture mode, with the former being 0.5 N / m and the latter being that no "bond break between the fiber-reinforced sheet (CFSS) and the bonding material (PCM)" was observed in any of the test pieces.

[0090] [Test to confirm the presence or absence of mixed layer formation] Using a SEM-EDS (JSM-IT500HR scanning electron microscope manufactured by JEOL Ltd.), the voltage was 10 kV and the observation mode was backscattered electron imaging, and elemental analysis was performed on the interface. By mapping the distribution of each element of Si, Ca, and C, it was confirmed whether or not there was an overlapping layer of Ca and C near the interface between the primer layer 22 and the binder layer 52.

[0091] [Base material] The base material used was a 40mm x 40mm x 160mm mortar bar cut in half to obtain a 40mm x 40mm x 80mm mortar piece.

[0092] [Polymer Cement Mortar 50] Based on Refremolset D manufactured by Sumitomo Osaka Cement Co., Ltd., 1.1 wt% high-strength polyethylene fiber with a length of 9 mm and an aspect ratio of 750 was added as reinforcing organic fiber, and a polymer cement mortar was formulated with fine aggregate having a maximum diameter of 0.45 mm, an FM value of 1.02, and a W / P ratio of 22.0 wt%.

[0093] [Preparation of test specimens] In Examples 1 and 2 and Comparative Examples 1 to 4, the type of primer used was changed as follows, and test pieces were prepared and the above-mentioned various tests were carried out.

[0094] [Example 1] In Example 1, FP Primer FP-EE from Nippon Steel Chemical & Material Co., Ltd. was used as the water-based epoxy primer 20. This primer is a two-liquid type having a base agent and a curing agent. In Example 1, no additives were added to the primer. The primer is a non-hazardous material (i.e., a non-combustible material) that does not fall under the category of hazardous material under the Fire Service Act.

[0095] [Example 2] In Example 2, a primer containing 1.00% of a silane coupling agent was used in addition to the primer used in Example 1 (FP Primer FP-EE manufactured by Nippon Steel Chemical & Material Co., Ltd.). The primer is a two-part type having a base agent and a curing agent. The primer is a non-hazardous material (i.e., a non-combustible material) that does not fall under the category of hazardous materials under the Fire Service Act.

[0096] [Comparative Example 1] In Comparative Example 1, FP-WEC manufactured by Nippon Steel Chemical & Material Co., Ltd. was used instead of the water-based epoxy primer 20. The primer is a two-liquid oil-based epoxy primer having a base agent and a curing agent. In Comparative Example 1, no additives were added to the primer. The primer is classified as a hazardous material (i.e., a combustible material) under the Fire Service Act.

[0097] [Comparative Example 2] In Comparative Example 2, Lion Bond A manufactured by Sumitomo Osaka Cement Co., Ltd. was used instead of the water-based epoxy primer 20. The primer is a two-liquid acrylic emulsion having a base agent and a curing agent. In Comparative Example 2, no additives were added to the primer. The primer is a non-hazardous material (i.e., a non-combustible material) that does not fall under the category of hazardous materials under the Fire Service Act.

[0098] [Comparative Example 3] In Comparative Example 3, ER Bond #55 manufactured by Elephone Chemical Industries Co., Ltd. was used instead of the water-based epoxy primer 20. This primer is a two-liquid water-dilutable epoxy primer. In Comparative Example 3, no additives were added to the primer. This primer is a designated flammable material under the Fire Service Act when diluted with water.

[0099] [Comparative Example 4] In Comparative Example 4, OS Primer Epo W manufactured by Obanaya Cementix Co., Ltd. was used instead of the water-based epoxy primer 20. The primer is a one-liquid type water-based epoxy primer. In Comparative Example 4, no additives were added to the primer. The primer is a non-hazardous material (i.e., a non-combustible material) that does not fall under the category of hazardous material under the Fire Service Act.

[0100] [Test results of Examples 1 and 2 and Comparative Examples 1 to 4] As shown in FIG. 12, in Examples 1 and 2 and Comparative Examples 1 and 2, the test results of the three-point bending test were 5.0 N / mm 2 On the other hand, in the three-point bending test, Comparative Examples 3 and 4 had a value of 5.0 N / mm 2 It was less than. Therefore, it was confirmed that Examples 1 and 2 and Comparative Examples 1 and 2 have higher adhesion performance than Comparative Examples 3 and 4, have equivalent adhesion performance to Comparative Example 1, and have higher adhesion performance than Comparative Example 2. In particular, it was confirmed that Example 2, which contains 1.00% of the silane coupling agent, has even higher adhesion performance than Example 1 in the three-point bending test using the test pieces after exposure. For Examples 1 and 2 and Comparative Examples 1 and 2, adhesion strength tests were also conducted according to the Construction Research Institute method. As a result, it was confirmed that Examples 1 and 2 had the same adhesion performance as Comparative Example 1 both before and after exposure, as shown in FIG. 12. However, for Comparative Example 2, a decrease in adhesion strength was observed in a three-point bending test using the test pieces after exposure. As described above, it was confirmed that Examples 1 and 2 had the same adhesion performance as Comparative Example 1, and had higher adhesion performance than Comparative Examples 2, 3, and 4, as shown in FIG. Therefore, a one-way shear test was carried out on Example 1 together with Comparative Example 2. The failure mode was the failure of the primer layer, and the failure mode was the failure of the primer layer at 11.2 N / mm 2 In contrast to Comparative Example 2, which showed a peel fracture energy of 19.8 N / mm, Example 1 showed a favorable fracture mode of cohesive failure of the polymer cement mortar and a peel fracture energy of 19.8 N / mm 2 The results showed a high peel fracture energy, indicating a high reinforcing effect. Furthermore, the coating locations of the primer and binder in Example 1 and Comparative Examples 1 to 4 were mapped for Si, O, and Ca elements using SEM-EDS. It was confirmed that in Example 1, a mixed layer was formed by overlapping C in the primer layer with Ca in the binder layer, and that the abundance ratio of C element in the mixed layer was about 10% higher than in the binder layer, whereas in the Comparative Examples, the overlap between C in the primer layer and Ca in the binder layer was weak or not observed.

[0101] The present invention is not limited to the above-described embodiment, and various modifications, changes, and improvements are possible without departing from the spirit and scope of the present invention. [Explanation of symbols]

[0102] 10 Reinforcement structure 20 Water-based epoxy primer 22 Primer layer 29 Mixed layer 40 Fiber Reinforced Sheet 42 Reinforced Fiber 43 Fiber-reinforced plastic wire 45 Wire fixing material 47 Matrix Resin 50 Polymer cement mortar 52 Binder layer 90 Structures 90A Reinforced surface 140 Fiber Reinforced Sheet 144 Fiber layer 146 Supporter layer

Claims

1. In a reinforcement structure of a structure in which a reinforcing material made of fiber-reinforced plastic containing reinforcing fibers is bonded to the surface of the structure using a bonding material, a primer layer formed of an aqueous epoxy primer having an aqueous epoxy resin base and a curing agent; a binder layer disposed on a surface of the primer layer, formed of polymer cement mortar as the binder, and having a mixed layer of the aqueous epoxy primer and the polymer cement mortar at the boundary with the primer layer; A reinforcing structure for a structure comprising:

2. The reinforcing material is A fiber-reinforced sheet in which a plurality of fiber-reinforced plastic wires are aligned in a longitudinal direction in a curtain-like shape and the fiber-reinforced plastic wires are fixed to each other with a wire fixing material; Fiber-reinforced plastic lattices, A plate made of fiber-reinforced plastic, and Fiber-reinforced plastic rod The reinforcement structure for a structure according to claim 1, wherein the reinforcement structure is any one of the above.

3. The reinforcing material is embedded within the binder layer; The surface of the reinforcing material is formed with projections and recesses. A reinforcement structure for a structure according to claim 1.

4. The reinforcing material has a surface on which powder having an average particle size of 0.900 mm or less is applied at a rate of 0.2 to 2.0 kg / m 2 Attached The reinforcement structure for a structure according to claim 3.

Citation Information

Patent Citations

  • Reinforcement of structure

    JP1991224901A

  • Structure reinforcing method

    JP2008063758A

  • Method for reinforcing structure

    JP2011208352A